Bank liberalisation : its impact on local banks' retail banking business. - Lim, Benny Tse Mien. (2008)
Major liberalisation measures has been introduced by MAS in 1998 and 1999. The FYP studies the impact on local banks with the coming in of new foreign banks(QFBs).